Pengaruh Non Performing Financing (NPF) dan Beban Operasional Pendapatan Operasional (BOPO) terhadap Financing Deposit Ratio (FDR) di Bank Syariah Indonesia - Miftakhul Jannah; Pujo Gunarso (University of Merdeka Malang, 2020)
The purpose of this study is to determine the effect of Non Performing Financing (NPF) and Operational Expenses Operating Income (BOPO) partially and simultaneously on Financing Deposit Ratio (FDR) in Banks Syariah Indonesia, as well as knowing the most dominant variable influencing the Financing Deposit Ratio (FDR) variable at Bank Syariah Indonesia. This study uses quantitative methods with multiple linear regression analysis techniques with the help of SPSS Version 24, while the hypothesis is proven using the statistical test t (partial test) and the statistical test F (simultaneous test). The type of data used in this study is secondary data, namely the Annual Report of Bank Syariah in Indonesia which is listed on the Indonesia Stock Exchange in the period 2015-2018. The results of this study, based on the statistical test t (partial test) showed that the Non Performing Financing (NPF) variable partially had a negative or no significant effect on the FDR variable, while the Operational Expense Operating Income (BOPO) variable partially had a positive or significant effect on the variable Financing Deposit Ratio (FDR). From the results of the F statistical test (simultaneous test) explained that the NPF and BOPO variables together (simultaneously) affect the FDR variable. Based on the results of the statistical test t variable that is most dominant in influencing the dependent variable namely Financing Deposit Ratio (FDR) is the Operating Expense Operating Income (BOPO) variable because of the value of sig. of the BOPO variable is smaller than the value of sig. (0.05) which is 0.003.